Methodical Maintenance of Management of Logistic Activity of the Trade Enterprise: Economic and Legal Support - PYLYPENKO, Andriy A.; SAVYTSKA, Nataliia L.; VAKSMAN, Regina V.; UHODNIKOVA, Olena I.; SCHEVCHENKO, Viktoriia S. (Journal of Advanced Research in Law and Economics, 2019)
The dynamism of the development of trade relations in the international arena requires from the domestic trade enterprises the introduction of effective tools of activity management, among which logistics are defined. The article explores the methodological bases of the analysis of the internal environment of logistic activity by determining the main logistical flows of a trade enterprise and indicators for their evaluation. The basic methods of carrying out the analysis of the external environment of the logistic activity of a trade enterprise have been determined and compared. An algorithm for building a logistic strategy of a trade enterprise has been formed. The basic legal principles of regulation of logistic activity of a trade enterprise have been specified.